Rethinking John Boyne’s The Boy in the Striped Pyjamas as Children’s Literature - Nugraheni Bhakti Prajaningtyas; Ida Rochani Adi (Lexicon, 2020)
This graduating paper aims to examine whether or not John Boyne’s novel entitled The Boy in the Striped Pyjamas should be categorized as children’s literature. The story tells about a nine-year-old German boy named Bruno with his Jewish friend, Shmuel, who lives inside the concentration camp during the Holocaust. This graduating paper applies the genre approach since it is the most suitable approach to analyze the elements of children’s literature genre, which are character and characterization, didactic elements, the happy ending, and element of pictures in children’s literature. In order to support the analysis, library research was conducted alongside the novel itself as well as supporting articles from reliable websites. The result of the analysis shows that John Boyne’s The Boy in the Striped Pyjamas cannot be categorized as children’s literature as the characteristics of children’s literature suggested by Nodelman are not found in the novel. However, The Boy in the Striped Pyjamas can be categorized as high literature since the characteristics of high literature are primarily found in the novel.